Інтродукція і селекція плодових культур: досягнення та перспективи розвитку досліджень - Moroz, P.A.; Kudrenko, I.K. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
Achievements of scientists of fruit bearing plants acclimatization department are showed. Main long-term trends of researches are determined.